Association Between Intraoperative Anesthesia Handover and Patient Morbidity and Mortality: a Systematic Review and Meta-Analysis - Yun-Tai Yao; Aubrey Samost-Williams; Loay Allafy; Aditya More; Willy W Lin; Yu-Fei Li; Mark Chao; Adriana Baranov; Valerie L Anderson; Rita Chamoun; Mert Tore; Vaishakh Tharavath; et al. (Anesthesia & Analgesia, 2026)
BACKGROUND: Intraoperative anesthesia handovers (IAHs) are common during prolonged procedures and shift-based staffing, but their association with postoperative outcomes remains uncertain. We performed an updated systematic review and meta-analysis to evaluate whether IAH, compared with no IAH, is associated with postoperative morbidity and mortality in surgical patients. METHODS: We searched PubMed, Embase, and Cochrane databases from inception to July 10, 2025, without language restriction. Eligible studies were observational studies or randomized controlled trials (RCTs) comparing patients with versus without IAH and reporting postoperative mortality or morbidity. Because of substantial clinical and methodological heterogeneity, narrative synthesis was the primary approach. As an exploratory analysis, adjusted odds ratios (aORs) were pooled using the generic inverse variance method with a random-effects model only for studies reporting adjusted effect estimates for clinically comparable composite short-term postoperative morbidity and mortality outcomes. Studies reporting mortality alone, morbidity alone, unadjusted estimates only, or noncomparable outcome definitions were summarized narratively. Sensitivity analyses excluded studies with distinct populations or designs, including the RCT, pediatric cohort, and thoracic surgery cohort. RESULTS: Thirteen studies were included, comprising 12 retrospective cohort studies and 1 multicenter RCT, representing 5 additional studies compared with the largest previous meta-analysis and including 1 RCT not available in previous quantitative syntheses. Overall, 1030,883 patients were included, 170,746 patients (16.6%) of whom experienced IAH and 860,137 did not. Seven studies, comprising 6 retrospective cohort studies and 1 RCT and involving 485,623 patients, contributed to the exploratory meta-analysis of composite short-term postoperative morbidity and mortality. The included studies varied substantially in surgical populations, definitions of IAH, outcome definitions, data sources, and adjustment strategies. The multicenter RCT found no significant effect of IAH on 30-day mortality, readmission, or postoperative complications. In the exploratory pooled analysis, IAH was not significantly associated with composite postoperative morbidity and mortality (aOR = 1.04; 95% confidence interval [CI], 0.98–1.11; P = 0.18; I 2 = 72%). Sensitivity analyses excluding the RCT, pediatric cohort, or thoracic surgery cohort yielded similar nonsignificant findings. CONCLUSIONS: Current evidence does not support a consistent independent association between IAH and increased postoperative morbidity and mortality. However, substantial heterogeneity and residual confounding limit causal interpretation. Future prospective studies should clarify context-specific risks and evaluate standardized IAH interventions.